The Relationship Of The Qualitty Of Health Services To The Satisfaction Of Patients Using BPJS At Rajeg Health Center - Kholifah, Siti; Marsepa, Eva; Rohmah, Meynur (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
There has been a decrease in patient visits from BPJS participants at Rajeg health centers in 2022 by 591,700, in 2023 by 581,776, and in 2024 by 199,940 patient visits. The decline that occurred was possibly caused by a lack of comfort and empathy, therefore there was a lack of relationship between the patient and the nurse. So there is a decrease in visits every year to the Rajeg Health Center. This research is to determine the relationship between the quality of health services and patient satisfaction using the “Social Security Administering Agency” (BPJS) which uses five dimensions, namely reliability, responsiveness, assurance, empathy and physical evidence. The research design used in this research is a quantitative approach with a descriptive correlation design. Sample The sampling technique in this research uses a non-probability sampling method using accidental sampling technique. The sample used was 255 respondents. Data analysis used in this research is the chi-square test by looking at the correlation coefficient value. The results of this research are that the quality of service, namely in the satisfaction category, is (71.8%) and patient satisfaction with BPJS users is (75.3%). In the statistical results, the p-value = 0.000 < 0.05, therefore, it can be concluded that there is a relationship between the quality of health services and the satisfaction of patients using BPJS.